Frailty transitions and health care use in Europe. (30th September 2019) - Sicsic, Jonathan; Rapp, Thomas
Abstract: Objective: There is relative consensus that chronic conditions, disability, and time‐to‐death are key drivers of age‐related health care expenditures. In this paper, we analyze the specific impact of frailty transitions on a wide range of health care outcomes comprising hospital, ambulatory care, and dental care use. Data Source: Five regular waves of the SHARE survey collected between 2004 and 2015. Study Design: We estimate dynamic panel data models on the balanced panel (N = 6078; NT = 30 390 observations). Our models account for various sources of selection into frailty, that is, observed and unobserved time‐varying and time‐invariant characteristics. Principal Findings: We confirm previous evidence showing that frailty transitions have a statistically significant and positive impact on hospital use. We find new evidence on ambulatory and dental care use. Becoming frail has greater impact on specialist compared to GP visit, and frail elderly are less likely to access dental care. Conclusions: By preventing transitions toward frailty, policy planners could prevent hospital and ambulatory care uses. Further research is needed to investigate the relationship between frailty and dental care by controlling for reverse causation.